Developing a methodological tool for exploring sense of safety in religious spaces - Anne Birgitta Pessi; Henrietta Grönlund; Ruth Illman; Ruth Illman; Ritva Palmén; Meri-Anna Paloniemi; Teemu Pauha; Jenni Spännäri (Frontiers in Psychology)
Emotions are a fundamental part of human existence, a power that massively affects our thinking and actions. Even after the affective turn in social sciences, religion is to a very large extent overlooked in the sociology of emotions. Then, psychological research on sense of safety often leaves the societal and political contexts of emotions unattended. Sense of safety—the topic of our study—provides an excellent topic to explore emotions as social, societal, spatial, and embodied phenomenon. Our article concerns the ways in which sense of safety is both constructed and contested in religious spaces and how to study the topic. The aim of this article thus is to develop a methodological tool for empirically exploring the sense of safety experienced in the spaces of religion. The article first discusses sense of safety and space, specifically in relation to religion, and the need for a methodological approach to investigating it empirically. The article leans on environmental psychology, urban studies, and research on the recognition and politics of belonging from political philosophy. Based on this, we design The Spiral Model: a one-plus-five dimensions tool for empirical exploration of sense of safety in religious spaces, and the dimensions are: Identifying a religious place; Unpacking intergroup connectedness, and networks of belonging and safety; Focusing on intragroup boundaries, and how they are afforded by physical surroundings; Exploring the embodied emotions that are associated with the place and its spatial dimension; and, Looking at the embodied emotions of sense of safety of inter- and intragroup nexuses in the framework of wider social, societal, and global vistas. To demonstrate how the model can be applied, for both data collection and analysis, we introduce four ongoing, collaborative empirical case studies: (1) a novel communal church building, (2) LGBTQ+ Muslims, (3) Jewish mikveh baths, and (4) intersections of dance and religion. Although the spiral model developed in this article is far from complete, it holds a lot of potential for advancing a more holistic view of humans in research and deepening the understanding of social space with philosophical conceptualization and analysis related to recognition and politics of belonging.